Three Levels Model for Differentiated Pharmacist Clinical Activities in the Community Pharmacy - the Proposal - Mónica Condinho; Margarida Cavaco; Fernando Miranda; Carlos Sinogas (Formifarma, LDA., 2014)
Due to the weak implementation of the change of pharmaceutical profession focus from the product to the patient, a new concept of services, based on pharmaceutical consultations should be developed and implemented. The aim of this paper is to introduce a new organizational model for pharmaceutical care services provision in the community pharmacy to answer differentiated patient's health needs. According to the model, pharmacist activities are structured in three interconnected levels, depending on patient´s health needs and expectations. Level 1 is the basic level of services provided by all the pharmacy professionals and addressed to customers asking for a comfort product or a medicinal product in the absence of non-controlled health problem. Level 2 is the pharmaceutical generalist service provided by a resident pharmacist and addressed to patients with common non-controlled health problems or asking for a specific and personalized counseling. It could be provided over-the-counter or in the office, configured as pharmaceutical consultation. Level 3 is the pharmaceutical specialized service, the Pharmacotherapeutic Follow-up consultation, provided by a specialized pharmacist, external to the pharmacy and is addressed to patients with recurrent non-controlled health problems or complex situations. The provision of pharmaceutical care services through differentiated pharmacist intervention levels, based on the pharmacy customer´s health needs, seem to be a suitable model for its routine implementation in the community pharmacy. Most of the previously identified barriers for real implementation of clinical services in the pharmacy can be pulled down by the new strategy here proposed.